2020
DOI: 10.1177/0003134820942194
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity Predicts Urban Gun Violence

Abstract: Introduction Food insecurity (FI), defined as inadequate access to affordable and quality nutrition, has negative health consequences. FI and violence share similar root causes. The aim of this study was to determine the association of FI with gunshot injury (GSI) incidence. Methods We performed a retrospective review of all patients from 2012 to 2018 who sustained a GSI. Food access data was abstracted from the US Department of Agriculture. We analyzed the impact of FI, low food access (LA), and low food acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Food insecurity was found to be independently associated with rates of violent firearm injury, which has been reported in prior studies. Using the United States Department of Agriculture’s Food Access Research Atlas, Smith et al 18 showed that FI was associated with urban gun violence in Atlanta, Georgia. Other studies have shown a similar finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food insecurity was found to be independently associated with rates of violent firearm injury, which has been reported in prior studies. Using the United States Department of Agriculture’s Food Access Research Atlas, Smith et al 18 showed that FI was associated with urban gun violence in Atlanta, Georgia. Other studies have shown a similar finding.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Smith et al found that FI was independently associated with an increased risk of firearm related injury for Atlanta's urban population. 18 Despite these findings, the link between FI and gun-related trauma is still understudied, with limited studies in most U. S. cities and data generally obtained from an aggregate level. The aim of this study was to investigate the association between area-level FI and gun violence in New Orleans, Louisiana, a region with high levels of FI and significant rates of gun violence.…”
mentioning
confidence: 99%
“…Additionally, prior work by our investigative team employed similar methods. 4 Hence, community-level FI statistics were used as the gold standard and were subsequently compared to results of the screening questionnaire for each participant. Contingency tables were utilized to determine sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of the survey.…”
Section: Methodsmentioning
confidence: 99%
“…3 Additionally, Smith and colleagues determined FI is an independent correlate of firearm injury incidence. 4…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation